2019
DOI: 10.1136/gutjnl-2018-317977
|View full text |Cite
|
Sign up to set email alerts
|

Immune cell trafficking and retention in inflammatory bowel disease: mechanistic insights and therapeutic advances

Abstract: Intestinal immune cell trafficking has been identified as a central event in the pathogenesis of inflammatory bowel diseases (IBD). Intensive research on different aspects of the immune mechanisms controlling and controlled by T cell trafficking and retention has led to the approval of the anti-α4β7 antibody vedolizumab, the ongoing development of a number of further anti-trafficking agents (ATAs) such as the anti-β7 antibody etrolizumab or the anti-MAdCAM-1 antibody ontamalimab and the identification of poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
77
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(93 citation statements)
references
References 130 publications
1
77
0
8
Order By: Relevance
“…These data demonstrate that molecular MRI of MAdCAM-1 unmasks active inflammation in chronic lesions of the intestinal tract. Overall and in line with our current knowledge of immune cell trafficking in IBD( 6 ), MPIO-αMAdCAM-1 act as leucocyte mimicking particles and display increased binding to the endothelium of the mucosa in both acute and chronic colitis ( Figure 3I ).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…These data demonstrate that molecular MRI of MAdCAM-1 unmasks active inflammation in chronic lesions of the intestinal tract. Overall and in line with our current knowledge of immune cell trafficking in IBD( 6 ), MPIO-αMAdCAM-1 act as leucocyte mimicking particles and display increased binding to the endothelium of the mucosa in both acute and chronic colitis ( Figure 3I ).…”
Section: Resultssupporting
confidence: 82%
“…At the molecular level, mucosal vascular addressin cell adhesion molecule 1 (MAdCAM-1) represents an interesting biomarker for mucosal inflammation( 6 ). Indeed, inflammation in mucosal tissue is associated with several phenotypical changes including activation of the endothelial cells of the lamina propria( 7 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-α4β7 antibody vedolizumab is successfully used for the treatment of IBD since 2014 [3,8] and has been shown to inhibit immune cell homing to the inflamed gut [9,10] indicating that cell trafficking is a central event in the pathogenesis of IBD [11]. Randomized controlled trials [3,8], as well as several real-world cohorts [12][13][14], demonstrated the efficacy and safety of vedolizumab in ulcerative colitis (UC) and Crohn's disease (CD).…”
Section: Introductionmentioning
confidence: 99%
“…For inflammatory bowel diseases, such as CD and ulcerative colitis, it has been reported that intestinal immune cell trafficking has been identified as a central event in the pathogenesis of diseases. Additionally, cell adhesion is a pivotal step in several aspects of immune cell trafficking [23]. In Fisher, interferon gamma was highly ranked, and the broader concept cytokine was also highly ranked.…”
Section: Resultsmentioning
confidence: 99%